Two terphenyl‐based diol hosts and corresponding solvent inclusions with dimethylformamide and acetonitrile. Issue 9 (7th August 2015) - Klien, Hendrik; Seichter, Wilhelm; Skobridis, Konstantinos; Weber, Edwin
<x xml:space="preserve">Abstract</x> Having reference to an elongated structural modification of 2, 2′‐bis(hydroxydiphenylmethyl)biphenyl, (I), the two 1, 1′:4′, 1′′‐terphenyl‐based diol hosts 2, 2′′‐bis(hydroxydiphenylmethyl)‐1, 1′:4′, 1′′‐terphenyl, C44H34O2, (II), and 2, 2′′‐bis[hydroxybis(4‐methylphenyl)methyl]‐1, 1′:4′, 1′′‐terphenyl, C48H42O2, (III), have been synthesized and studied with regard to their crystal structures involving different inclusions, i.e. (II) with dimethylformamide (DMF), C44H34O2·C2H6NO, denoted (IIa), (III) with DMF, C48H42O2·C2H6NO, denoted (IIIa), and (III) with acetonitrile, C48H42O2·CH3CN, denoted (IIIb). In the solvent‐free crystals of (II) and (III), the hydroxy H atoms are involved in intramolecular O—H...π hydrogen bonding, with the central arene ring of the terphenyl unit acting as an acceptor. The corresponding crystal structures are stabilized by intermolecular C—H...π contacts. Due to the distinctive acceptor character of the included DMF solvent species in the crystal structures of (IIa) and (IIIa), the guest molecule is coordinated to the host via O—H...O=C hydrogen bonding. In both crystal structures, infinite strands composed of alternating host and guest molecules represent the basic supramolecular aggregates. Within a given strand, the O atom of the solvent molecule acts as a bifurcated acceptor. Similar to the solvent‐free cases, the hydroxy H atoms in inclusion structure (IIIb) are involved in intramolecular hydrogen bonding, and there is thus a lack of host–guest interaction. As a result, the solvent molecules are accommodated as C—H...N hydrogen‐bonded inversion‐symmetric dimers in the channel‐like voids of the host lattice.